2020
DOI: 10.3233/jad-191183
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in in vivo Alzheimer’s Disease Neuropathology in Late Middle-Aged Hispanics

Abstract: Background: Females may have a higher risk of dementia than males. It is not clear if sex differences in Alzheimer's disease (AD) neuropathology explain the higher risk of dementia in females. Sex differences in AD neuropathology might begin in middle age, decades before the sex differences in dementia are apparent. Objective: To examine sex differences in in vivo AD neuropathology in late middle age. Methods: We conducted a cross-sectional comparison of AD biomarkers among 266 Hispanic males and females (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“… 63 However, sex differences in amyloid pathology in elderly individuals are controversial. Worse amyloid PET pathology was reported in men in cohorts 70 to 85 years old, 64 while in cohorts of ∼64‐year‐olds 65 and 40‐ to 60‐year‐olds, 66 women exhibited worse amyloid pathology, particularly during menopause transition. It is tempting to speculate that sexual dimorphism in amyloid pathology may vary depending on age.…”
Section: Discussionmentioning
confidence: 94%
“… 63 However, sex differences in amyloid pathology in elderly individuals are controversial. Worse amyloid PET pathology was reported in men in cohorts 70 to 85 years old, 64 while in cohorts of ∼64‐year‐olds 65 and 40‐ to 60‐year‐olds, 66 women exhibited worse amyloid pathology, particularly during menopause transition. It is tempting to speculate that sexual dimorphism in amyloid pathology may vary depending on age.…”
Section: Discussionmentioning
confidence: 94%
“…The analysis of inequalities depending on sex aims to enrich the analysis and generates a more rigorous knowledge of reality. Already classic studies point to the need of contemplating the sex variable as an important modulating factor in both the encoding and decoding of emotions (Zuckerman et al, 1979) and, currently, this approach is identified as a growing field of scientific study (Abbruzzese et al, 2019;Luchsinger et al, 2020;Sullivan et al, 2017). Attending to brain dimorphism, it would be convenient to perform analyses of performance in experimental tasks including the variable "sex" (Pletzer, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…MK‐6240 PET scans (n = 320) were gathered from participants in various ongoing studies at Columbia University Irving Medical Center (CUIMC). These include the Washington Heights Inwood Columbia Aging Project 23 (n = 4), the Northern Manhattan Study of Metabolism and Mind (NOMEM) 24 (n = 200), the VALAD (Valacyclovir Treatment of Alzheimer's Disease) study 25 (n = 57), and other studies recruiting participants at CUMC 26 (n = 59). These studies—as well as the current study—were reviewed by the institutional review board, and all participating subjects gave consent for all procedures.…”
Section: Methodsmentioning
confidence: 99%